2003
DOI: 10.1002/bdrc.10020
|View full text |Cite
|
Sign up to set email alerts
|

Muscle‐derived stem cells: Potential for muscle regeneration

Abstract: Duchenne muscular dystrophy (DMD) is a devastating X-linked muscle disease characterized by progressive muscle weakness caused by the lack of dystrophin expression at the sarcolemma of muscle fibers. Although various approaches to delivering dystrophin in dystrophic muscle have been investigated extensively (e.g., cell and gene therapy), there is still no treatment that alleviates the muscle weakness in this common inherited muscle disease. The transplantation of myoblasts can enable transient delivery of dyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 83 publications
1
46
0
2
Order By: Relevance
“…Regardless of the passage number, the cell proliferative activity remained high. In the present study, the cellular morphology, attachment time, and growth features were similar to the aforementioned MDSC characteristics reported by Huard et al (2003).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regardless of the passage number, the cell proliferative activity remained high. In the present study, the cellular morphology, attachment time, and growth features were similar to the aforementioned MDSC characteristics reported by Huard et al (2003).…”
Section: Discussionsupporting
confidence: 88%
“…Since MDSCs can differentiate into muscle, endothelial, and nerve cells, they might serve as a promising tool for the treatment of ED. According to Huard et al (2003), MDSCs possess the biological characteristics of low adhesion, round shape, small size, high refractive index, and low proliferation rate. After 48 h of culture, cell attachment was accomplished and the cells gradually expanded into a polygonal shape.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In contrast with embryonic stem cells (ESCs), that nonetheless raise ethic controversy, the majority of human adult stem cells are difficult to expand in culture to the scale required for possible therapeutic applications without loss of pluripotency. In the past few years, several types of adult stem cells have been isolated from different sources and tested for their capability of rescuing the phenotype of several diseases, including muscular dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Desmin is intermediate filament protein, one ingredient of the cytoskeleton, which is specifically expressed in muscle fibers, and positive desmin immunostaining confirmed that the isolated cells were myogenic. Original satellite cells express the transcription factor PAX7, while activated satellite cells express both PAX 7 and MyoD (Huard et al 2003). As activated satellite cells proliferate and differentiate, the expression of PAX 7 is downregulated, and the myogenic regulatory factors Myf5, MyoD, myogenin and MRF4 are only found in activated satellite cells, where they mediate the activation of skeletal muscle specialization genes and induce the differentiation of satellite cells (Seale and Rudnicki 2000).…”
Section: Discussionmentioning
confidence: 99%